A Game-Changer to Short-Term Rentals in Spain - Sánchez-Cubo, Francisco; Viana Lora, Alba (Wiley, 2025)
Usually, when it comes to short-term rentals (STRs), there are three approaches: prohibition, limitation or laissez-faire. Using experimental data on STRs from the National Statistics Institute, we analyse the fluctuations in their figures in all municipalities in Spain to determine whether there is a link between the type of regulation and its effects. Plus, we discuss the most recent sentence, which allows a new way of regulating STRs and becoming a game-changer in the near future.
https://openpolicyfinder.jisc.ac.uk/id/publication/7482
Keywords: Viviendas de alquiler turístico - España; Alojamientos turísticos - Derecho y legislación; Regulation; Spain; Short-term rentals; Tourism